1991
DOI: 10.1111/j.1464-5491.1991.tb01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Education Improves Knowledge, Compliance, and Foot Problems in Type 2 Diabetes

Abstract: Despite the established role of foot care education in diabetes management, reports evaluating such interventions are rare. The effectiveness of an intensive foot care intervention programme and a conventional one were therefore compared in Type 2 diabetes. The intensive group showed significantly greater improvements than the conventional group in foot care knowledge (p less than 0.001), compliance with the recommended foot care routine (p = 0.012), and compliance with the initial advice to consult a podiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
6

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(84 citation statements)
references
References 4 publications
2
76
0
6
Order By: Relevance
“…These procedures are in agreement with another study and the Brazilian Diabetes Society guidelines (15)(16) .…”
Section: Characterization Of the Study Population According To Sociodsupporting
confidence: 58%
“…These procedures are in agreement with another study and the Brazilian Diabetes Society guidelines (15)(16) .…”
Section: Characterization Of the Study Population According To Sociodsupporting
confidence: 58%
“…Litzelman et al (62) noted a decrease in serious foot lesions at 1 year after an intervention consisting of group education, with three follow-up visits, provider guidelines, and chart reminders. Other studies failed to demonstrate improvements with interventions (41,46,63). Malone et al (64) found a significant decrease in foot ulcer and amputation rates, although this study had significant methodological inadequacies.…”
Section: Process Measuresmentioning
confidence: 93%
“…Both individual (38,39,66 -68) and group (72,75,93) lifestyle interventions had positive effects on diet and self-care behaviors. It is notable that skills teaching was effective in both group (41,62) and individual settings (45,58).…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…Results of randomized controlled trials selected for a systematic review (10) indicate that foot self-care behavioral change is short-lived (11)(12)(13)(14)(15). This finding could be attributable to the fact that these interventions have focused solely on foot self-care knowledge and behavioral skills training, and none has addressed the psychosocial processes underlying patients' foot self-care.…”
mentioning
confidence: 87%